Women Linguistic Features Used by Elle Evans in The Kissing Booth 2 Movie - Ni Putu Sheila Damota; I Made Suastra; Luh Putu Laksminy (Research and Community Services Institutes of Udayana University, 2022)
Language makes people understand each other and interact in daily life. Most importantly, language has become an important tool in communication. The way men and women speak is different. They have different features although they speak the same language. The title of this undergraduate thesis is